Hermeneutics as theological prolegomena a canonical approach - Scalise, Charles J. (Macon, GA Mercer University Press, 1994)
Contents: The Crisis: Revelation as Theological Prolegomena -- The Categories: Cross-Disciplinary Theological Hermeneutics -- Canon: Childs' Approach to Biblical Interpretation -- Canonical Hermeneutics: Post-Critical Theological Prolegomena -- Conclusion: Towards a Canonical Model of the Doctrine of God. Includes bibliographical references and index.
Keywords: Childs, Brevard Springs, -- 1923-; Bible -- criticism, canonical; Bible -- hermeneutics; Revelation; Doctrine, theology